EFFECT OF DISTILLATION DURATION ON ESSENTIAL OIL YIELD AND COMPOSITION OF LAVENDER LAVANDULA ANGUSTIFOLIA GROWN IN IRAQ - A. S. Alhasan; M. Sh. Alrawi; D. T. Al-Ameri; A. F. Almehemdi (مجلة الأنبار للعلوم الزراعية, 2025)
Lavender is a medicinal and aromatic crop grown worldwide for essential oil (EO) production that is used in the pharmaceutical, ecofriendly pesticides, foods, perfumery, cosmetics, and other industries. However, the quantity and quality of lavender EO is affected by several factors including the extraction process. This study examined the effect of distillation time (DT) on the quantity and quality of the EO obtained from dried lavender flowers through the hydro-distillation process. Different distillation times ranging from 10 to 180 min were applied in isolating the EO from dried lavender flowers using a Clevenger-type apparatus while gas chromatography-mass spectrometry (GC-MS) identified the chemical compositions derived from the oils. The maximum EO of 2.15% was obtained after 150 min distillation and the minimum (0.16%) at 10 min. In all the analyzed samples, the chemical composition of the isolated EO revealed the dominance of cyclohexanol (4.64-16.33%), cyclohexanone (3.42-10.77%), eucalyptol (1.04-6.06%), caryophyllene oxide (2.94-5.23%), caryophyllene (2.89- .74%), nerol oxide (1.12-196%), trans-carveol (0.32-1.66%), and β-ocimene (0.46-0.89%). The results suggest that distillation time affects the yield of EO and the quantity of some constituents in dried lavender flowers